Assessment Probability of Soil Liquefaction Potential Based on SPT Data with NovoLIQ Application - Oktafiani, Pradyta Galuh; Sasmayaputra, Nur Alfian (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2025)
Liquefaction is a geological phenomenon that occurs when soil loses its strength due to a shock, such as an earthquake, and becomes semi-liquid. Liquefaction usually occurs in water-saturated sandy soils that are subjected to seismic stress. During an earthquake, the pore water pressure in the soil increases, causing the soil grains to lose contact with each other and resulting in the soil becoming unstable and behaving like a liquid. This process can have serious impacts on building structures and the infrastructure above them, such as foundation shifts, building tilting, and structural collapse. The Kulonprogo area is one of the areas that has a variety of soil types ranging from silt to sandy with a shallow groundwater table and is one of areas that according to BMKG, the Kulonprogo area is included in the area that has the potential to be affected by megathrust. Seeing from this, the Kulonprogo area has a high liquefaction potential. Based on this, this research will calculate the liquefaction potential in the Kulonprogo area using soil Cone Penetration Test data. Cone Penetration Test testing is carried out to a depth of 30 meters to evaluate the characteristics of soil layers and obtain N-SPT values that reflect the density and strength of the soil in each layer. The results of SPT testing at depths of up to 30 meters show a variety of soil types ranging from low plasticity silt in the upper layers to sand. The results obtained obtained the CRR value on average at each depth is 0.4 with SF between 1.04-1.68 which has a Liquefaction potential according to Youd and Nobel's theory of 80.2% and according to Centin's theory of 100%. This makes the Kulonprogo area have a high potential for Liquefaction, especially if a megathrust earthquake occurs.